Determination of phenanthrene and fluoranthene in rice samples by activated carbon-based dispersive solid phase micro-extraction coupled with gas chromatography-flame ionization detector analysis - Nahrowi, Nurul Nadjwa; Boon, Yih Hui; Shahriman, Mohamad Shariff; Yahaya, Noorfatimah; Mohd Zain, Nur Nadhirah; Asman, Saliza; Khan, Md Firoz; Sambasevam, Kavirajaa Pandian; Lim, Vuanghao; Raoov, Muggundha (2020)
A simple dispersive solid phase micro-extraction (DSPME) based on activated carbon (AC) was performed for the determination and separation of carcinogenic polycyclic aromatic hydrocarbons (PAHs), namely phenanthrene and fluoranthene, in selected white, brown and parboiled rice samples. The extraction was coupled with gas chromatography-flame ionization detector (GC-FID) for analysis. Under the optimized conditions [amount of adsorbent (5 mg), sample volume (40 mL), type (dichloromethane), and volume of desorption solvent (300 μL)], calibration curves were found to be linear for the concentration between 10 and 1000 μg kg-1 with coefficient of determination (R2) from 0.9938 to 0.9955. The limit of detection (LOD) and limit of quantification (LOQ) were in the range of 0.11 - 0.15 μg kg-1 and 0.33 - 0.46 μg kg-1, respectively. Relative standard deviation (RSD) was less than 8.02% and 5.48% for intra-day (n = 5) and inter-day (n = 5) for the present method, respectively. High pre-concentration factor (2587 - 2866) and satisfactory recoveries (90.23 - 115.63%) were also achieved. The proposed method was found to be simple, rapid and reliable for the monitoring of PAHs in rice samples.